Molecular acoustic technology is in technological process of cryopreservation - Коваленко, Евгений Николаевич (Technology audit and production reserves, 2012)
In the article nizkointensivnaya is described acoustic technology and electronic system on determination of optimum parameters of acoustic vibrations for affecting mikroob'ekty of zoons of KRS (spermii, embryos) before their kriokonservaciey